EFFICACY OF VARIOUS DRUG FORMS OF LYCOPENE IN PATIENTS WITH DYSLIPIDEMIA - P. Ya. Dovgalevsky; V. A. Klochkov; N. E. Chalyk; O. M. Ansimova; I. Petyaev (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To find the optimal scheme of lycopene application and to compare clinical efficacy of two lycopene presentations produced on the basis of 1) vegetable oil and 2) milk protein (lactolycopene) in patients with dyslipidemia.Material and methods. At the first step of the study to choice an optimal scheme of pharmacotherapy efficacy of three schemes of lycopene (lactolycopene) application was compared in three groups of patients (n= 27, 25 and 28 respectively) with ischemic heart disease, dyslipidemia and high level of lipid peroxygenation (LPO). At the second step two groups of patients (n=28 and 31) with dyslipidemia received lycopene in the same dose at the same time but in different presentations. Patients of the first group received oil solution of lycopene in capsules, patients of the second group — a powder of lactolycopene dissolved in 100 ml of boiled water. Levels of total cholesterol (TC), high density (HDC) and low density cholesterol (LDC), triglycerides (TG) and LPO activity marker, malondialdehyde (MDA), were studied. The duration of each study step was 8 weeks.Results. Lactolycopene 10 mg QD for the night was as effective as 10 mg TID (30 mg per day) in normalization of the lipid metabolism parameters and malondialdehyde level due to chronopharmacological mechanism. Similar efficacy of the evening lactolycopene reception 10 mg QD and 30 mg QD was due to the saturation of tissues with an antioxidant. Lactolycopene application led to significant reduction in levels of TC (from 247.1±27 to 186.5±12 mg/dl; p<0.001), LDC (from 150.9±17 to 119.3±8 mg/dl; p<0.001), TG (from 165.8±12 to 128±10 mg/dl; p<0.001) and MDA (from 2.67±0.2 to 1.3±0.07 nM/ml; p<0.001) unlike reception of oil solution of lycopene.Conclusion: Lactolycopene has higher effect on lipid metabolism and LPO in comparison with this in lycopene in oil solution presentation. An optimal scheme of lactolycopene reception is 10 mg for the night.